Alienação parental sob o olhar do Serviço Social: limites e perspectivas da atuação profissional nas varas de família - Lima, Edna Fernandes da Rocha (2016)
Parental alienation has been widely debated in Brazil by areas of law and psychology, especially in the last ten years. This phenomenon respect to family life of children and adolescents is a topic little explored by the Social Work. Thus, this thesis was to study the object of the analysis of view of social Judiciary workers on parental alienation and the law dealing with the subject. It started from the hypothesis that professionals working in family courts, although dealing with many family disputes, including parental alienation, have not discussed and deepened this. To verify this hypothesis, the research aimed at understanding how to have the first discussions about parental alienation in Brazil and the path to the adoption of Parental Alienation Law, then, to know and analyze the perceptions and actions of social Judiciary assistants in relation to the family, parental alienation and Law No. 12.318/2010 and the contribution of these professionals in identifying the phenomenon through social expertise. The methodological process was based on the historical and social analysis of the legislation on justice and family and the concepts of family and parental alienation, deepening the different positions in the Brazilian reality. Was conducted a quantitative and qualitative survey in the period 2013-2105, being interviewed the social workers who work in family courts and social analyzed reports in which parental alienation manifested itself both from the professional look as through determination court to carry out the technical expertise. The speech content analysis of the interviews and the reports identified as the conceptions of family and parental alienation direct the technical performance of each professional. It was considered that the methodology used, especially the quantitative and qualitative research with the interviewed who manifest spontaneously about subject and allowed the identification of objective and subjective aspects of the discourse. The results show that the subject in question requires a thorough discussion by the professional category and the contribution of the social worker in cases involving parental alienation should be guided by the promotion of guaranteeing the right to family life